Phylogenomic data resolved the deep relationships of Gymnogynoideae (Selaginellaceae) - Zhao, Jing; He, Zhao-Rong; Fang, Shao-Li; Han, Xu-Ke; Jiang, Lu-Yao; Hu, Yu-Ping; Yu, Hong; Zhang, Li-Bing; Zhou, Xin-Mao (Frontiers in Plant Science, 2024)
The unresolved phylogenetic framework within the Selaginellaceae subfamily Gymnogynoideae (ca.130 species) has hindered our comprehension of the diversification and evolution of Selaginellaceae, one of the most important lineages in land plant evolution. Here, based on plastid and nuclear data extracted from genomic sequencing of more than 90% species of all genera except two in Gymnogynoideae, a phylogenomic study focusing on the contentious relationships among the genera in Gymnogynoideae was conducted. Our major results included: (1) Only single copy region (named NR) and only one ribosomal operon was firstly found in Afroselaginella among vascular plants, the plastome structure of Gymnogynoideae is diverse among the six genera, and the direct repeats (DR) type is inferred as the ancestral state in the subfamily; (2) The first strong evidence was found to support Afroselaginella as a sister to Megaloselaginella. Alternative placements of Ericetorum and Gymnogynum were detected, and their relationships were investigated by analyzing the variation of phylogenetic signals; and (3) The most likely genus-level relationships in Gymnogynoideae might be: ((Bryodesma, Lepidoselaginella), (((Megaloselaginella, Afroselaginella), Ericetorum), Gymnogynum)), which was supported by maximum likelihood phylogeny based on plastid datasets, maximum likelihood and bayesian inference based on SCGs dataset and concatenated nuclear and plastid datasets, and the highest proportion of phylogenetic signals of plastid genes.